The Cross Section of Stock Returns before World War I - Grossman, Richard S.; Shore, Stephen H. (Journal of Financial and Quantitative Analysis, 2006)
Abstract We examine the cross section of stock returns using an original dataset consisting of annual observations on price, dividends, and shares outstanding for nearly all stocks listed on U.K. exchanges between 1870 and 1913, supplemented with additional information about attrition. The only clear pattern in the historical U.K. data is the high returns of extremely small stocks. Among the largest 99.8% of stocks, the historical U.K. data do not display the pattern found in modern U.S. (CRSP) data of excess returns for small stocks or stocks with poor past performance. Unlike CRSP data, stocks that do not pay dividends do not outperform stocks that pay small dividends during this period. However, as in the modern data, there is a weak relation between dividend yield and performance for stocks that pay dividends.